Comparison between plasma lactate and lactate clearance with the impact of acute phase complication in burn injury patient - Hamilton Lowis; Sachraswaty R. Laidding; Fonny Josh; Yudhy Arius; Fritz Nasuhuly; Joko Hendarto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Severe burn can cause rapid loss of intravascular volume with resultant adecrease in peripheral blood flow which reduces tissue oxygen transport and inturn, increases plasma lactate. Plasma lactate and lactate clearance are usefulparameters to compare complicated and uncomplicated burn patients in theacute phase. The study aimed to evaluate the initial and 24-h plasma lactatelevels as well as lactate clearance as useful parameters to assess acute phasecomplications of burn patients. This was a cross-sectional study involving35 burn patients who admitted at Abdul Wahab Sjahranie District Hospital,Samarinda during the period of September 2018 to September 2019. Thestudy was immediately begun after admission of the patients. Plasma lactatelevels were measured at admission and24-h after the first measurement. Theacute phase complication was assessed 72 h after burns from the laboratoryparameter. Fisher’s exact test and t test using SPSS software version 24wereapplied for statistical analysis. The 24-h plasma lactate level (p= 0.001) andplasma lactate clearance (p = 0.002) were significantly correlated with theoccurrence of acute phase complications of burns. However, the initial plasmalactate level was not significantly correlated (p = 0.609). In conclusion, there isa significantly correlation between 24-h plasma lactate level and plasma lactateclearance are with the occurrence of acute phase complications of burns.